Characteristics of carbon, nitrogen, phosphorus and sulfur cycling genes, microbial community metabolism and key influencing factors during composting process supplemented with biochar and biogas residue. (December 2022) - Wang, Nanyi; Zhao, Keqi; Li, Fanghong; Peng, Hua; Lu, Yaoxiong; Zhang, Lihua; Pan, Junting; Jiang, Shilin; Chen, Anwei; Yan, Binghua; Luo, Lin; Huang, Hongli; et al.
Graphical abstract: Highlights: Highest relative abundance of functional genes related to C degradation and N cycling. Biogas residue better promoted bacterial and fungal diversity during composting. Biochar significantly promoted the abundance of Humicola. Diversity of bacteria and fungi increased during the cooling and maturation periods. Temperature, pH, EC were the main factors affecting the microbial community. Abstract: Carbon (C), nitrogen (N), phosphorus (P), and sulfur (S) cycling functional genes and bacterial and fungal communities during composting with biochar and biogas residue amendments were studied. Correlations between microbial community structure, functional genes and physicochemical properties were investigated by network analysis and redundancy analysis. It was shown that the gene of acsA abundance accounted for about 50% of the C-related genes. Biogas residue significantly decreased the abundance of denitrification gene nirK. Biogas residues can better promote the diversity of bacteria and fungi during composting. Biochar significantly increased the abundance of Humicola . Redundancy analysis indicated that pile temperature, pH, EC were the main physicochemical factors affecting the microbial community. WSC and NO3 − -N have significant correlation with C, N, P, S functional genes. The research provides a theoretical basis for clarifying the metabolic characteristics of microbial communities during composting and for the application of biochar and biogas residues in composting.